Taxpayer Understanding of Tax Obligations in the Digital Era - Tarmui, Elda Purwanti; Imahda Khoiri Furqon (Department of Public Administration, 2025)
This study explores taxpayers’ understanding of tax obligations in the digital era, focusing on how digital transformation affects compliance behavior and awareness. The rapid digitalization of tax administration through systems such as e-filing, e-billing, and e-registration has reshaped the interaction between taxpayers and tax authorities. However, the success of these innovations depends largely on the taxpayers’ ability to comprehend both regulatory provisions and technological procedures. Using a qualitative descriptive approach, this study analyzes secondary data from government reports, academic journals, and previous empirical research to identify patterns in taxpayer behavior and comprehension. The findings reveal that digital literacy, awareness, and knowledge of tax procedures are key determinants of compliance in a technology-driven environment. Taxpayers with sufficient understanding tend to demonstrate higher levels of voluntary compliance and trust in the digital tax system. Conversely, low digital competence and limited understanding hinder optimal utilization of online services. The study emphasizes the importance of education, outreach, and user-friendly digital infrastructure as strategies to strengthen taxpayer compliance in the digital age. These findings contribute to the broader discussion on how to achieve a transparent, efficient, and inclusive digital tax administration in Indonesia.